VALIDITY AND RELIABILITY OF NURSING INTERVENTION CLASSIFICATION: SELF-CARE ASSISTANCE ON PATIENTS WITH STROKE - Intansari Nurjannah (Belitung Nursing Journal, 2019)
Background: Nursing intervention is part of nursing process. The accurateness of intervention needs to be explored through an effort to measure validity and reliability of the intervention. Objectives: This study aimed to investigate the validity and reliability of four Nursing Intervention Classifications (NICs) of Self-Care Assistance (SCA) on patients with stroke. Methods: Validity measurement involved 4 experts, while reliability involved 7 samples for each NIC. Validity was analyzed using content validity index (I-CVI and S-CVI), while reliability was analyzed using kappa and percent agreement. Results: Sixteen activities of NICs (I-CVI score less than 0.78) were eliminated and two activities considered not applicable. The results of reliability were above 0.85 kappa value with 85% of percent agreement. Conclusion: Elimination of not valid activities increased reliability.